2021
DOI: 10.1021/acschembio.1c00223
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescent Probes for the Detection of Cancer-Associated Proteases

Abstract: Proteases are enzymes capable of catalyzing protein breakdown, which is critical across many biological processes. There are several families of proteases, each of which perform key functions through the degradation of specific proteins. As our understanding of cancer improves, it has been demonstrated that several proteases can be overactivated during the progression of cancer and contribute to malignancy. Optical imaging systems that employ near-infrared (NIR) fluorescent probes to detect protease activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 129 publications
0
29
0
Order By: Relevance
“…25–31 In particular, activity-based NIR fluorescent probes have gained attention due to their outstanding advantages in the field of detection and bioimaging. 32–34 These advantages include high specificity, good sensitivity, deep tissue penetration as well as a high signal-to-noise ratio, which can effectively prevent false positive signals. 35 However, due to the lack of an ideal fluorophore platform, smart NIR fluorescent probes are very challenging to fabricate.…”
Section: Introductionmentioning
confidence: 99%
“…25–31 In particular, activity-based NIR fluorescent probes have gained attention due to their outstanding advantages in the field of detection and bioimaging. 32–34 These advantages include high specificity, good sensitivity, deep tissue penetration as well as a high signal-to-noise ratio, which can effectively prevent false positive signals. 35 However, due to the lack of an ideal fluorophore platform, smart NIR fluorescent probes are very challenging to fabricate.…”
Section: Introductionmentioning
confidence: 99%
“…While our previously reported sulfonated CyBams were not suitable for this application, the installation of a tertiary amine into the norcyanine framework dramatically improves cellular and in vivo signals, likely due to enhanced lysosomal uptake and retention. It is likely that these “lysotracker-like” norcyanines and the resulting CyLBam probes will have applications in other settings, including their use as activity-based sensing agents. , …”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these "lysotracker-like" norcyanines and the resulting CyLBam probes will have applications in other settings, including their use as activity-based sensing agents. 61,62 In applying this approach for ADC applications, we assume that the fluorescent probe can serve as a useful surrogate for the payload component. Here we have shown that quantitative comparisons of linker chemistries can be obtained by varying the linker component.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In recent years, our research group and others have focused on the preparation of several classes of fluorescent compounds [9][10][11][12][13][14][15][16]. Antitumor compounds with fluorescent properties, optical probes activated by enzymes [17][18][19][20][21][22], fluorescent amino acids and synthetic peptides for imaging studies [23][24][25][26][27][28][29][30], and more recently, boron-dipyrromethene (BODIPY) derivatives [31][32][33][34][35][36][37][38][39][40] have been the targets of many investigations.…”
Section: Introductionmentioning
confidence: 99%